Heavy Metals in the Soil Around a Cement Company in Sokoto, Northwestern Nigeria Pose Health Risks - Yahaya, Tajudeen; Umar, Abdulrazak; Abubakar, Muddassiru; Abdulazeez, Abdulmalik; Musa, Bilyaminu; Ibrahim, Yusuf (Tecno Scientifica Publishing, 2023)
Cement is widely used in the building industry because it is reliable and because its basic ingredients are inexpensive and abundant. However, the production of cement produces heavy metal-laden dust that can harm humans and the environment. This study aimed to determine the risk posed by heavy metals in the soil around a cement company in Sokoto, Nigeria. Soil samples were obtained at 0.1, 0.5, and 1.0 km from the company and served as test samples, while control samples were obtained at 5.0 km away. The soil samples were treated and assayed for lead (Pb), cadmium (Cd), copper (Cu), and zinc (Zn) using atomic absorption spectroscopy. The values obtained were used to estimate the heavy metals’ average daily inhalation (ADI), average daily dermal exposure (ADDE), hazard quotient (HQ), health risk index (HRI), and carcinogenic risk (CR). Permissible levels of all the heavy metals were detected at all the locations (0.1 > 0.5 > 1.0 > 5.0 km). However, the ADI, ADDE, HQ, HRI, and CR of the heavy metals were above the permissible limits. It can be inferred from the results that the soil around the company can predispose humans to heavy metal toxicities. Consequently, the company needs to prioritize pollution control.